Higher education governance in France, Germany, and Italy: Change and variation in the impact of transnational soft governance. Issue 1 (1st March 2017) - Dobbins, Michael; Knill, Christoph
Abstract: There is a consensus that transnational soft governance has unleashed the forces of change in higher education. However, individual national HE systems are still anchored in country-specific regulatory regimes, which reflect national-historical, institutional, and cultural developments. Against this background, three crucial questions guide our study: How does the state react to transnational pressures for change? How is transnationally inspired policy change 'digested' by the preexisting country-specific governance structures? And to what extent have national HE systems converged on a common governance model? To address these questions, we conduct a multi-level comparative analysis of developments in Germany, France, and Italy. We first break down the concept of higher education governance into sub-dimensions and derive concrete policy indicators for three historically embedded governance ideal types. Drawing on historical institutionalism and institutional isomorphism, we explore how historical legacies and transnational communication have impacted policy pathways over the past 30 years. We graphically illustrate the policy trajectories using our 'governance triangles', which encompass the balance of power between multiple actors, including the state and universities, university management and the academic profession, and external stakeholders.